2019
DOI: 10.1108/heswbl-05-2019-0072
|View full text |Cite
|
Sign up to set email alerts
|

Managing risks in work-integrated learning programmes: a cross-institutional collaboration

Abstract: Purpose Work-integrated learning (WIL) poses legal, reputation, operational, strategic and financial risks for higher education providers (HEPs). The purpose of this paper is to explore how HEPs can manage five significant WIL risks involving intellectual property, student disability and medical conditions, the host organisation and the legal literacy of WIL practitioners. Design/methodology/approach This paper is a cross-institutional collaboration of WIL practitioners who explored risk management in WIL pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It is evident from the discussion that whilst educators may lead the development of WIL curriculum, without the active engagement of students and industry, gaps in graduates' “work-readiness” will persist. Whilst difficulties for educators in sourcing (Cameron et al , 2019), and for employers in providing (Jackson et al , 2017) suitable placements have been acknowledged in the literature, this study further highlights that curriculum development and delivery would benefit from educator-industry-student partnerships which enables tripartite learning. The discussion also highlights the complexity in meeting the “work-readiness” needs of multiple stakeholders, with industry engagement in CDL required to reduce dissatisfaction in hospitality graduates which affects employee turnover.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is evident from the discussion that whilst educators may lead the development of WIL curriculum, without the active engagement of students and industry, gaps in graduates' “work-readiness” will persist. Whilst difficulties for educators in sourcing (Cameron et al , 2019), and for employers in providing (Jackson et al , 2017) suitable placements have been acknowledged in the literature, this study further highlights that curriculum development and delivery would benefit from educator-industry-student partnerships which enables tripartite learning. The discussion also highlights the complexity in meeting the “work-readiness” needs of multiple stakeholders, with industry engagement in CDL required to reduce dissatisfaction in hospitality graduates which affects employee turnover.…”
Section: Discussionmentioning
confidence: 78%
“…Whilst the traditional perspective has placed responsibility for developing employable graduates on higher education institutes (Hurrell, 2016), the role of multiple stakeholders in producing work-ready and future proof graduates is debated in the literature (Ferns et al , 2016). The discourse highlights the role of industry in sharing the responsibility for developing student capabilities with educators (Cameron et al , 2019), with industry partners considered to play a vital role in providing authentic industry placements (Smith and Worsfold, 2015) which provide students with learning opportunities (Horng et al , 2017). However, the key challenges to stakeholder engagement identified in “The WIL Report” (Patrick et al , 2008) and documented in the literature over the last decade are still in existence today (Ferns et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Collaboration lies implicit within the content of both above-presented definitions and is a core facet of WIL activities (see, for example, Cameron et al , 2020; Venville et al , 2021). Yet, within UW’s definition, a further possibility to use WIL as a professional research approach for collaborations within working life is opened.…”
Section: Conceptual Discussion Of Resident Participation and Work-int...mentioning
confidence: 99%
“…The study showed that organizations do a full evaluation of risks when doing a project, but mostly there is no systematic approach to risk management in organizations. Cameron, Ashwell, Connor, Duncan, Mackay, and Naqvi (2019) study showed the importance of organizations understanding that strategic expansion of integrated learning is likely to be accompanied by huge risks for stakeholders and there is a series of risk management practices in response to five major risks in programs to evaluate integrated learning that is applied by stakeholders in the work to improve the risk management framework in their organizations, improving legal literacy. It turns out that there are four topics: study balance, collaboration, Relationship Management, and resources which has been characterized as guidelines for stakeholders in risk management.…”
Section: Literature Reviewmentioning
confidence: 99%